Concordat versus agreements: experience of integration Church activity into the lithuanian legal system - Subačius, Paulius V. (Prawo Kanoniczne, 2018)
In the year 2000 after difficult searches for a consensus in the Church itself and after variable negotiations with Government three agreements between the Holy See and the Republic of Lithuania were signed and ratified. The first one – “Concerning juridical aspects of the relations between the Catholic Church and the State”, the second – “Concerning the pastoral care of Catholics serving in the Army”, and the third – “On Co-operation in Education and Culture”. A Mixed bilateral commission between the State and the Church has been constituted for elaboration and practical implementation of the aforementioned acts. An article analyses a shift from the drafts of concordat to agreements and tensions between Church and State in spheres of education, culture, social care, pastoral care in the military and hospitals.